Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.

hiya asked in Science & MathematicsMathematics Β· 1 decade ago

Can someone explain this math problem to me?

I'm proving that the derivative of cotx = (-cscx)^2

the first step is:

let y = (cosx)/(sinx)

the second step is:

[ (-sinx)(sinx) - cosx(cosx) ] / (sinx)^2

Please explain why and how this SECOND step was performed. Thank you!

1 Answer

Relevance
  • Anonymous
    1 decade ago
    Favorite Answer

    y = u/v ---> y ' = (u ' v - u v ')/v^2

    with u = cosx ---> u ' = -sinx

    v = sinx --> v ' = cosx

    plug in formula

Still have questions? Get your answers by asking now.